Regionale Sprache als Identitätsmarker Hamburger Fußballfans.: Eine Projektskizze - Neumann, Lara (Linguistik Online, 2019)
The dissertation project Regionale Sprache als Identitätsmarker. Zur Konstruktion sozialer Bedeutung bei Hamburger Fußballfans ‘Regional language as identity marker. The construction of social meaning among football fans in Hamburg’ examines different practices of identity construction of fans from the two football clubs FC St. Pauli and Hamburger Sportverein (HSV). By analysing a group interview with HSV fans, this paper investigates the potential of identification with regional language. Identity constructions can be identified in the following three aspects: (a) the conceptualisation of the local substandard, (b) the speakers’ positioning concerning the use of the local substandard and (c) language attitudes.